Risk Management for Florida 4-H Youth Development Work: Records and Contracts - Dale Pracht; Paula Davis; Janet Psikogios; Marilyn Norman; Kate Fogarty; Jean Hink; Kathy Hartman; Candi Dierenfield; Melinda Souers (EDIS, 2024)
This is one part of the series Risk Management for 4-H Youth Development Work.